Respuesta :

9514 1404 393

Answer:

  -2 11/35

Step-by-step explanation:

Put the numbers where the variables are and do the arithmetic.

  [tex]\left(\dfrac{x^2}{x}-3\right)\div10\cdot z=\left(\dfrac{(-6)^2}{1.2}-3\right)\div10\cdot\left(-\dfrac{6}{7}\right)\\\\=\left(\dfrac{36}{1.2}-3\right)\div10\cdot\left(-\dfrac{6}{7}\right)=(30-3)\div10\cdot\left(-\dfrac{6}{7}\right)\\\\=\dfrac{27}{10}\cdot\left(-\dfrac{6}{7}\right)=-\dfrac{27\cdot6}{10\cdot7}=-\dfrac{27\cdot3}{5\cdot7}=\boxed{-\dfrac{81}{35}=-2\dfrac{11}{35}}[/tex]

__

It is important to note here that the order of operations requires that the only value being divided by is 10, not 10z. The division by 10 occurs before the multiplication by z.